2015
DOI: 10.1155/2015/301796
|View full text |Cite
|
Sign up to set email alerts
|

Cone-Beam Computed Tomographic Assessment of Mandibular Condylar Position in Patients with Temporomandibular Joint Dysfunction and in Healthy Subjects

Abstract: Statement of the Problem. The clinical significance of condyle-fossa relationships in the temporomandibular joint is a matter of controversy. Different studies have evaluated whether the position of the condyle is a predictor of the presence of temporomandibular disorder. Purpose. The purpose of the present study was to investigate the condylar position according to gender in patients with temporomandibular disorder (TMD) and healthy controls using cone-beam computed tomography. Materials and Methods. CBCT of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 41 publications
5
31
0
Order By: Relevance
“…[9][10][11] Nonconcentric condyle-fossa relationships have been associated with abnormal TMJ function. 10,[12][13][14][15][16][17][18] However, in other studies, 4,5,13,[19][20][21][22] the presence or absence of temporomandibular disorder (TMD) did not correlate with the condyle position in the TMJ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Nonconcentric condyle-fossa relationships have been associated with abnormal TMJ function. 10,[12][13][14][15][16][17][18] However, in other studies, 4,5,13,[19][20][21][22] the presence or absence of temporomandibular disorder (TMD) did not correlate with the condyle position in the TMJ.…”
Section: Introductionmentioning
confidence: 99%
“…Some research has noted the influence of occlusion in the condylar process-mandibular fossa relationship, 4,5,10,[13][14][15][27][28][29][30][31][32][33] while others have not. 4,5,13,[19][20][21][22] Studies have found that the condyles were positioned more anteriorly, 4,5,10,[13][14][15]27,28 posteriorly, 27,29,30 intermediately, 27 superiorly 27,28,31,32 and inferiorly 33 in various occlusal, skeletal, and facial relationships. In addition to condylar position, occlusion might be related to the articular eminence angle or slope 13,14,28 and articular eminence height, 14,16,17 or the vertical height of the fossa 13,19,28,31 and anteroposterior and mediolateral thickness of the condylar head.…”
Section: Introductionmentioning
confidence: 99%
“…1 Plain film radiography, conventional tomography, computed tomography (CT), conebeam computed tomography (CBCT), and magnetic resonance imaging (MRI) are different radiographic methods that have been used in previous studies for TMJ assessment. 6,7 Cone-beam computed tomography is suggested as a high resolution and precise 3-dimensional (3D) technique for analyzing the condylar position in the glenoid fossa. 8 Some of the reasons why CBCT is preferred when compared with other imaging techniques at the region of TMJ are as follows: 3D images, higher accuracy and a smaller slice thickness as compared to the conventional tomography and radiography 6 ; spatial resolution even higher than in the case of spiral CT 6 ; effective dose and scanning time, and cost lower than in spiral CT 6,8 ; the fact that MRI is not suitable for the evaluation of hard tissue.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies deny this association. 6 The condylar movements and pathways during mouth opening and closing are different, depending on the condylar position in the glenoid fossa. Physical loading on the articular disk and the condylar head would also be different in various condylar positions.…”
Section: Introductionmentioning
confidence: 99%
“…Since in TMD patients an apparent association between condylar position and clinical findings worth to be treated is lacking [46], it appears that the often asked question of “the most physiological” or “the most optimum” condylar position in intercuspal position is more of academic interest than of clinical relevance. Instead, a relatively broad range of equally acceptable positions exists [36].…”
Section: Discussionmentioning
confidence: 99%